2019
DOI: 10.3390/app9071339
|View full text |Cite
|
Sign up to set email alerts
|

The Technological Design of Geometrically Complex Ti-6Al-4V Parts by Metal Injection Molding

Abstract: In this study, the metal injection molding (MIM) process is applied to produce Ti-6Al-4V parts using blended and prealloyed powders, respectively. The feedstocks are prepared from a polyformaldehyde-based binder system with a powder loading of 60 vol%, exhibiting a low viscosity. The decomposition behavior of the binders is investigated and the thermal debinding procedure is designed accordingly. The debound parts are subsequently sintered at 1200 and 1300 °C. The results show the mechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…At present, the interaction of the binder and powder is mainly assessed by rheological and thermogravimetry measurements [3,[15][16][17]. Very little is known about the specific interactions among binder components and how such interaction affects the MIM of reactive powders, such as Ti-MIM.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the interaction of the binder and powder is mainly assessed by rheological and thermogravimetry measurements [3,[15][16][17]. Very little is known about the specific interactions among binder components and how such interaction affects the MIM of reactive powders, such as Ti-MIM.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the melt flow in the cavity, the appearance of a frozen layer is the main reason for a reduction in the filling ability. To address this challenge, a number of methods have been tested, with the aim of reducing the filling pressure [ 7 ] and the viscosity of the melt material [ 8 , 9 , 10 ] or increasing the filling speed. When the aim was to increase the filling pressure, a high injection pressure was selected, and the experiment showed that the melt flow length was improved.…”
Section: Introductionmentioning
confidence: 99%